2021
DOI: 10.47119/ijrp1008911120212468
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study Correlation Between Grade and Amount of Mitosis With Er, Pr, and Her2 Expression in Invasive Breast Carcinoma of No Special Type

Abstract: Background:In 2018 there were about 24.2% new cases of breast carcinoma worldwide. Molecular breast carcinoma, like expression estrogen receptor (ER), progesterone receptor (PR),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…HER-2 having no correlation with the degree of histological differentiation of cancer cells means that HER-2 can be possessed by breast cancer cells with varying degrees of malignancy (Kristian & Sandhika, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HER-2 having no correlation with the degree of histological differentiation of cancer cells means that HER-2 can be possessed by breast cancer cells with varying degrees of malignancy (Kristian & Sandhika, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results of multivariate cox regression analysis showed that comorbidities/complications were not a signi cant factor affecting survival. A study by Kristian & Sandhika (2021), concluded that the increased degree of differentiation in cancer cells (grade) would be followed by a decrease in estrogen receptors and progesterone receptors in cancer cells, but there was no correlation between HER-2 examination results and the degree of histological differentiation of breast cancer cells. This shows that lower grade cancer cells have properties that are more similar to normal cells: they have estrogen and progesterone receptors and thus have lower cell growth rates compared to higher grade breast cancers that lose estrogen and progesterone receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of ER/PR in each breast cancer cell generally varies, so the response in each patient will be different. The higher expression of ER/PR in cancer cells, the better prognosis the patient has [6].…”
Section: Introductionmentioning
confidence: 99%